Innovative and streaming technologies in foreign languages lessons - Guljakhon Abduganievna Norimova (Peerian Journals Publishing, 2022)
The rapid development of the Internet, personal digital devices and high-speed data transmission technologies (the development of new methods, forms and technologies of teaching online training courses, training modules for undergraduate programs, streamlined learning technologies are gaining popularity). Stream (translated from English. Stream - stream) - a series of video or audio received by the user through the transmission of data. The term is also used by Internet users as a slang name for live streaming on video hosting
Keywords: Internet; personal digital devices; high-speed data